PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENGEMBANGKAN KARAKTER PESERTA DIDIK DENGAN BERBASIS KEARIFAN LOKAL DI SMAN 1 JABIREN - Tarita Aprilani Sitinjak; Ni Putu Diah Agustin Permanasuri; Tamara Apriliyana; Eko Wicaksono; Apriansyah (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2022)
Human resource development by applying innovative learning models so that they can develop positive characters based on local wisdom in Central Kalimantan. Apply the values ​​of huma betang (family and know each other), belum bahadat (behave politely), hapakat basara (consensus for consensus), handep (mutual cooperation), and not yet full of hinje simpei (live in harmony and peace) in the Project Based Learning learning method (PjBL). The purpose of this research is to find out how students’ character development based on local wisdom uses the Problem Based Learning model. This research is a type of field research, qualitative research. The research subjects were students of class X IPS 2 at SMAN-1 Jabiren. The instrument used in this research is the researcher himself. The results of the study stated that with the PjBL method the characteristics of tolerance, curiosity, activeness, openness to input, communication, respecting achievements and opinions of friends, accepting differences of opinion, and respecting teachers are characteristics that develop significantly. Character education in the world of education, both primary, secondary, and even higher education must be well integrated. The research implication is inovatif learning models based on local wisdom is applied.